A 122 GHz ISM-Band FMCW Radar Transceiver - Lammert, Vincent; Achatz, S.; Weigel, Robert; Issakov, V. (GeMIC 2020 - Proceedings of the 2020 German Microwave Conference, 2020)
In this work we present a 122 GHz FMCW radar module. It is based on an integrated transceiver in a 130nm SiGe technology. The chip is bonded to a PCB which contains the baseband circuits and the antennas. This paper discusses the design of the whole system around the transceiver IC, chip-to-PCB transition and the PCB antenna array. Finally, measurement results of a target at a distance of 6m are shown.
CRIS-Team Scopus Importer:2020-06-02
Keywords: D-band; ISM-Band; Radar; transceivers